Reference intervals for blood biochemical parameters in growing male water buffaloes (Bubalus bubalis) - de Oliveira, Camila Sabino [UNESP]; de Lima Francisco, Caroline [UNESP]; Marques da Silva, Daiane Cristina [UNESP]; de Castilhos, André Michel [UNESP]; Oba, Eunice [UNESP]; Mendes Jorge, André [UNESP] (Elsevier, 2025)
Reference intervals for blood variables in domestic animals are essential to diagnosing diseases and identifying physiological abnormalities in animal production. Establishing such intervals for water buffaloes is important due to the growing use of this species in livestock, their relevance as a major source of meat and milk, and the lack of specific reference data for certain categories within the species. This study evaluated the blood parameters in growing male water buffaloes. Seventy-five animals from three genetic groups (Jafarabadi, Mediterranean, and Murrah), with an initial body weight of 309.1 ± 60.6 kg and age of 13 ± 1.2 months, were used. All animals were clinically healthy and blood samples were collected from their jugular vein on days 0, 56, and 84. The concentrations of total protein, high-density lipoprotein (HDL), low-density lipoprotein (LDL), very low-density lipoprotein (VLDL), albumin, aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), creatinine, bilirubin (total, indirect, and direct), total cholesterol, glucose, lipoproteins, triglycerides, and leptin were analysed using commercial kits. Reference intervals, 90 % confidence intervals, means, standard deviations, and reference values were calculated according to the guidelines of the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) by excluding the upper and lower 2.5 % of values for each biochemical parameter. Sixteen blood biochemical parameters were characterised for growing male water buffaloes. The findings provide valuable data for interpreting health status and supporting management practices in water buffalo meat production systems.